Hot-corrosion resistance of dissimilar AISI 4340 and AISI 304L weldments in the molten salt environment at 600°C. (17th February 2017) - Arivarasu, M.; Venkatesh Kannan, M.; Devendranath Ramkumar, K.; Arivazhagan, N.
ABSTRACT: High temperature corrosion resistance of welded components in power plant industry, hot sections of gas turbines, boilers, industrial waste incinerators, metallurgical furnaces and petrochemical installations is one of the serious necessity. The failure of hot sections of welded component is due to the deposition of molten salt which accelerates the hot corrosion reactions in the weld joint. In this research work, the oxy-chlorination of dissimilar weldments between AISI 304L austenitic stainless steel and AISI 4340 alloy steel at 600°C in eutectic mixture of K2 SO4  + 60% NaCl under molten salt conditions was investigated. Corrosion kinetics for this dissimilar joints calculated from the thermogravimetric charts were represented. Corrosion on the dissimilar joint employing E309L filler in pulsed current gas tungsten arc welding process is found to be very aggressive, due to the fragmented delta ferrites at numerous locations resulting in the formation of the micro electrochemical cells, which act as sites for corrosion initiation and thus leading to higher corrosion rate. However, in the case of continuous current, the joint is able to protect itself better in this environment due to lower amounts of delta ferrites in weld zone, which is attributed to the higher temperature available in continuous mode leading to austenisation of delta ferrites in the multipass welding.